3D-printed medial arch supports of varying hardness versus a prefabricated arch support on plantar pressure: A 1-month randomized crossover study in healthy volunteers. Issue 2 (25th April 2023) - Channasanon, Somruethai; Praewpipat, Bongkoch; Duangjinda, Nitkamon; Sornchalerm, Lertchai; Tesavibul, Passakorn; Paecharoen, Siranya; Tanodekaew, Siriporn
Abstract : Background: Foot orthoses are commonly used as a noninvasive treatment to relieve foot pain. The custom full-length insoles with various materials and designs have been studied for their effectiveness in reducing plantar pressure. However, few studies have been conducted with respect to custom medial arch support on the relationships between material hardness and measured plantar pressure and level of comfort. Objectives: To evaluate the effects of the hardness of custom medial arch supports on plantar pressure and comfort perception. Study design: Randomized crossover study. Methods: Two custom silicone medial arch supports of varying hardness (A and B) were fabricated using 3D printing technology and tested in 12 healthy volunteers against a commercially prefabricated arch support (C). The volunteers wore three medial arch supports in a random order, one month for each arch support with 3–4 days of washout period before wearing the next one. The plantar pressure was measured and analyzed according to each foot zone: forefoot, midfoot, and hindfoot, comparing before intervention, immediately after intervention, and 1 month after intervention. The comfort perception was assessed by collecting volunteer feedback with a questionnaire after using each medial arch support. Results: After 1-month intervention, both 3D-printed and prefabricated medial arch supports demonstrated significantly higher average pressure in the midfoot ( P < 0.001), whereas significantly lower average pressure in the forefoot ( P < 0.001) and hindfoot ( P = 0.014, 0.026, and 0.018 for A, B, and C, respectively), compared with those before intervention. There were no significant differences in plantar pressure distribution between the 3D-printed and prefabricated medial arch supports. However, the 3D-printed medial arch supports resulted in better comfort than the prefabricated arch support. Conclusions: The material hardness had no apparent effect on plantar pressure distribution. The three medial arch supports showed reducing plantar heel pressure. Further research is needed to investigate the potential effect of 3D-printed silicone medial arch supports on reducing foot pain in patients.